2010
DOI: 10.1002/jms.1859
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolism of the α‐pyrrolidinophenone designer drug methylenedioxy‐pyrovalerone (MDPV) in rat and human urine and human liver microsomes using GC–MS and LC–high‐resolution MS and its detectability in urine by GC–MS

Abstract: Since the late 1990s, many derivatives of the α-pyrrolidinophenone (PPP) drug class appeared on the drugs of abuse market. The latest compound was described in 2009 to be a classic PPP carrying a methylenedioxy moiety remembering the classic entactogens (ecstasy). Besides Germany, 3,4-methylene-dioxypyrovalerone (MDPV) has appeared in many countries in Europe and Asia, indicating its worldwide importance for forensic and clinical toxicology. The aim of the presented work was to identify the phase I and II meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
161
2
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(186 citation statements)
references
References 23 publications
15
161
2
8
Order By: Relevance
“…In another study based on examination of rat urine, MDPV underwent a more complicated metabolism, including oxidative and hydroxylation steps. In this same study, MDPV was found to be metabolized in vitro by CYP isoenzymes 2C19, 2D6, and 1A2 [58].…”
Section: Metabolism: Pyrovaleronementioning
confidence: 67%
“…In another study based on examination of rat urine, MDPV underwent a more complicated metabolism, including oxidative and hydroxylation steps. In this same study, MDPV was found to be metabolized in vitro by CYP isoenzymes 2C19, 2D6, and 1A2 [58].…”
Section: Metabolism: Pyrovaleronementioning
confidence: 67%
“…Stimulant effects, an increase in libido, anxiety, hallucinations, and paranoid psychosis have been reported [6]. MDPV appears to undergo CYP450 2D6, 2C19, and COMT phase 1 metabolism into methylcatechol and pyrrolidine, which in turn are glucuronidated to allow for renal excretion [11,12]. Although the mechanism of action is not fully elucidated at this time, a dopaminergic mechanism is hypothesized due to the chemical similarity to amphetamines and the behavioral effects of MDPV that mimic those of amphetamines which are known to affect dopaminergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This likely represents recent exposure to these drugs, as per the patient's history, or could suggest decreased metabolism and excretion of the parent drugs. Studies show that both MDPV and halogenated cathinones undergo extensive hepatic metabolism [16,17]. Genetic heterogeneity in the metabolism of these drugs may play a role in cases of severe intoxications and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%